Improving Tenth Grade Students’ Vocabulary Competence Using Posters - Umamit, Darwati; Lestari, Hernina Dewi (UIBU, 2022)
English at the senior secondary school (SMA) level plays a crucial role in helping students develop communication skills and fostering an understanding of the importance of English for enhancing the nation’s competitiveness in the global arena. However, in practice, many students still experience difficulties with vocabulary, as revealed through interviews with the tenth-grade English teacher. Poster images serve as an effective and efficient instructional medium for delivering messages or information to students. By providing visual representations of objects along with their meanings, poster images can support students in expanding their vocabulary. This study aims to describe how the use of poster images improves vocabulary mastery among tenth-grade students at SMA Islam Baitur-Rohmah Malang in 2024. The findings from classroom observations and learning activities indicate an improvement in student performance. The average score in Cycle I was 65.5, increasing to 75.5 in Cycle II. In Cycle I, 15 students (58%) achieved mastery, while 10 students (42%) had not yet met the criteria. In Cycle II, all 25 students (100%) achieved mastery. These results show that all tenth-grade students successfully reached the expected minimum mastery level (>70%) in Cycle II, with the mastery rate increasing to 100%.